Governing biotechnology to provide safety and security and address ethical, legal, and social implications - Trump, Benjamin; Cummings, Christopher; Klasa, Kasia; Galaitsi, Stephanie; Linkov, Igor (Frontiers in Genetics, 2023)
The field of biotechnology has produced a wide variety of materials and products which are rapidly entering the commercial marketplace. While many developments promise revolutionary benefits, some of them pose uncertain or largely untested risks and may spur debate, consternation, and outrage from individuals and groups who may be affected by their development and use. In this paper we show that the success of any advanced genetic development and usage requires that the creators establish technical soundness, ensure safety and security, and transparently represent the product’s ethical, legal, and social implications (ELSI). We further identify how failures to address ELSI can manifest as significant roadblocks to product acceptance and adoption and advocate for use of the ‘safety-by-design’ governance philosophy. This approach requires addressing risk and ELSI needs early and often in the technology development process to support innovation while providing security and safety for workers, the public, and the broader environment. This paper identifies and evaluates major ELSI challenges and perspectives to suggest a methodology for implementing safety-by-design in a manner consistent with local institutions and politics. We anticipate the need for safety-by-design approach to grow and permeate biotechnology governance structures as the field expands in scientific and technological complexity, increases in public attention and prominence, and further impacts human health and the environment.